Synthesis and properties of biphasic calcium phosphate prepared by different methods - Ahmad Nawawi, Natasha; Ramesh, Singh; Hamdi, Mohd; Tan, Chou Young; Purbolaksono, Judha; Toulouei, Ranna; Sopyan, Iis (Trans Tech Publications, Switzerland, 2014)
Hydroxapatite (HA) is a stable phase with low dissolution rate in body fluid. Meanwhile, β-tricalcium phosphate (β-TCP) is rather soluble but the dissolution rate is too fast for bone bonding. Therefore a mixture of both is desirable to control the bioresorbability. In this work, calcium phosphate powder has been synthesized via sol gel and wet precipitation method to compare phase behaviour of these powders upon calcination. XRD result clearly revealed that both as-synthesized powders were pure HA with good purity. The decomposition of HA to TCP took place in the range of 700-800 °C and 800-900 °C for sol gel and wet chemical precipitation powder, respectively. The weight loss detected at 700-850°C in TGA analysis confirmed the presence of this biphasic mixtures. From FTIR analysis, profound change in OH- band intensity was attributed to the increased in HA crystallinity with calcination temperature.